The association of cervicovaginal Langerhans cells with clearance of human papillomavirus - Dai, Wenkui; Gui, Liming; Du, Hui; Li, Shuaicheng; Wu, Ruifang (Frontiers in Immunology, 2022)
Human papillomavirus (HPV) clearance is important in eliminating cervical cancer which contributes to high morbidity and mortality in women. Nevertheless, it remains largely unknown about key players in clearing pre-existing HPV infections. HPV antigens can be detected by the most important cervical antigen-presenting cells (Langerhans cells, LCs), of which the activities can be affected by cervicovaginal microbiota. In this review, we first introduce persistent HPV infections and then describe HPV-suppressed LCs activities, including but not limited to antigen uptake and presentation. Given specific transcriptional profiling of LCs in cervical epithelium, we also discuss the impact of cervicovaginal microbiota on LCs activation as well as the promise of exploring key microbial players in activating LCs and HPV-specific cellular immunity.